Deconstructing the Portrayal of the Creature in Mary Shelley’s Frankenstein - David Alfadillah; Firdiansyah Firdiansyah; Rahmat Fajar (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study analyzes the construction of the Creature's character in Mary Shelley's Frankenstein (1831) through Gérard Genette's narratology and Jacques Derrida's deconstruction. The main problems addressed are: (1) how is the portrayal of the Creature constructed through Victor Frankenstein's narrative?; and (2) how can this portrayal be deconstructed to challenge identity boundaries within the text? Using a qualitative descriptive method with close reading techniques, this research examines textual evidence from the 1831 edition of Frankenstein. The findings demonstrate that the Creature's monstrosity is not an absolute truth but an unstable subjective perspective constructed through narrative authority. Through deconstructive reading, contradictions emerge between Victor's claims and the Creature's self-narrative, proving that identity in the novel is contestative and open to reinterpretation. The final conclusion reveals that the 'monster' label is not an inherent trait of the Creature but a discursive mask created by Victor to conceal his own irresponsibility as a creator. By amplifying the Creature's voice, this study proves that the boundaries between human and monster are thin and fragile, showing that the creator can be more 'monstrous' than the being he created.